2015
DOI: 10.2174/1573406411666150105105529
|View full text |Cite
|
Sign up to set email alerts
|

Design of SGLT2 Inhibitors for the Treatment of Type 2 Diabetes: A History Driven by Biology to Chemistry

Abstract: A brief history of the design of sodium-dependent glucose cotransporter 2 (SGLT2) inhibitors is reviewed. The design of O-glucoside SGLT2 inhibitors by structural modification of phlorizin, a naturally occurring O-glucoside, in the early stage was a process mainly driven by biology with anticipation of improving SGLT2/SGLT1 selectivity and increasing metabolic stability. Discovery of dapagliflozin, a pioneering C-glucoside SGLT2 inhibitor developed by Bristol-Myers Squibb, represents an important milestone in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Between the years 1980 and 1990, sodiumglucose cotransporters-1 (SGLT1) and sodium-glucose cotransporters-2 (SGLT2) inhibitors were identi ied, as well as the bene its of phlorizine in the diabetic population primarily in animal models. In diabetic rats with to 90% pancreatectomy, it was discovered that phlorizine normalized fasting and postprandial glucose levels, with additional bene its in insulin resistance [14,15]. In contrast to the previously mentioned, phlorizine was not thought of a candidate for glucose lowering therapy, given a great number of limitations.…”
Section: History Of Type 2 Diabetes Mellitusmentioning
confidence: 99%
See 3 more Smart Citations
“…Between the years 1980 and 1990, sodiumglucose cotransporters-1 (SGLT1) and sodium-glucose cotransporters-2 (SGLT2) inhibitors were identi ied, as well as the bene its of phlorizine in the diabetic population primarily in animal models. In diabetic rats with to 90% pancreatectomy, it was discovered that phlorizine normalized fasting and postprandial glucose levels, with additional bene its in insulin resistance [14,15]. In contrast to the previously mentioned, phlorizine was not thought of a candidate for glucose lowering therapy, given a great number of limitations.…”
Section: History Of Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Given its similar properties to Cinchona extracts and weeping willow, it was proposed as a reasonable candidate to treat fever, some infectious diseases and even malaria. Approximately 50 years later, its glucosuric capacity at high doses was discovered [11,14,15]. It was also suggested that phlorizine induced diabetes in canine models, given that it caused similar symptoms with its chronic administration (glucosuria, polyuria and weight loss) [15].…”
Section: History Of Type 2 Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few years, since the crystal structure of hSGLT2 is not yet available, the strategies for developing new hSGLT2 inhibitors are limited to chemical synthesis, structure-activity relationships (SAR) analysis, and lead modification [26] [27] [28]. These strategies would be high cost and time-consuming in the process of new drug development and the results are also limited to the highly structural similarity.…”
Section: Introductionmentioning
confidence: 99%